2006
DOI: 10.1111/j.1600-0897.2006.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Toll‐Like Receptor (TLR) Agonists on TLR and Microbicide Expression in Uterine and Vaginal Tissues of the Mouse

Abstract: These results indicate that the uterus and vagina as well as uterine epithelial cells are responsive to bacterial and viral pathogens. Not only do epithelial cells respond to TLR agonists by releasing MCP-1, which mediates inflammatory responses, but they also influence the expression of selected TLR genes to further enhance innate immune protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 67 publications
4
38
0
Order By: Relevance
“…In contrast to cells grown in culture dishes, cells on inserts are polarized and are therefore more likely to remain functional in ways that reflect their existence within the Fallopian tube. Using mouse uterine epithelial cells, we compared freshly isolated cells with those grown to confluence on cell inserts and found that 5-10 days in culture had minimal effects of TLR expression (84). Whether growth in culture plates and cell passaging affect TLR expression in human FRT epithelial cells, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to cells grown in culture dishes, cells on inserts are polarized and are therefore more likely to remain functional in ways that reflect their existence within the Fallopian tube. Using mouse uterine epithelial cells, we compared freshly isolated cells with those grown to confluence on cell inserts and found that 5-10 days in culture had minimal effects of TLR expression (84). Whether growth in culture plates and cell passaging affect TLR expression in human FRT epithelial cells, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The lower compartment of the genital tract is continuously exposed to the external environment and must be able to distinguish between commensal microflora and pathogens (Kaushic 2011). In the non-pregnant female genital tract, expression of AMPs varies with site, which may promote tolerance to certain bacteria in the vagina, but effect elimination of pathogens in the uterine cavity (Soboll et al 2006). Production has been shown to be influenced by steroid hormones, and expression varies with the menstrual cycle (King et al 2003a(King et al , 2003b, suggesting a protective effect at key times such as menstruation and implantation.…”
Section: Amps In Pregnancymentioning
confidence: 99%
“…The endometrium is the first line of defense against microbial invasion, and endometrial epithelial cells are thought to play a key role in local innate immunity (Herath et al, 2006;Soboll et al, 2006;Turner et al, 2014). Endometrial epithelial cells line the uterine mucosal surface, forming a physical barrier to protect the host from pathogen invasion (Wira et al, 2005).…”
Section: Introductionmentioning
confidence: 99%